Analisis Pengaruh Pertumbuhan Ekonomi, Tingkat Pendidikan Dan Tingkat Pengangguran Terhadap Tingkat Kemiskinan di Kabupaten Probolinggo - Miftaqul Qoiriyah; Marseto Marseto; Anisa Fitria Utami (Pusat Riset dan Inovasi Nasional, 2025)
This study aims to analyze the effect of economic growth, education level, and unemployment rate on poverty rate in Probolinggo Regency during the period 2009–2023. The method used is a quantitative approach with multiple linear regression analysis based on annual secondary data. The results of the analysis show that education level has a negative and significant effect on poverty rate, while economic growth and unemployment rate do not have a significant effect. This finding indicates that improving the quality of education can be an effective strategy in reducing poverty rates. On the other hand, economic growth and decreasing unemployment are not strong enough to have a direct impact on reducing poverty in the region.